Uncovering and Informing Preservice Teachers’ Prior Knowledge About Poverty - Charlotte Anne Mundy; Melinda Marie Leko (Networks: An Online Journal for Teacher Research, 2015)
This study explored 30 preservice teachers’ knowledge on issues related to poverty. In an openended questionnaire, preservice teachers’ perceptions of poverty and how teachers should respond to students from poverty were explored. Results indicated that preservice teachers’ knowledge was nonspecific and lacked focus on the relationship among poverty, schools, and students. These results indicate a need for us as teacher educators to provide preservice teachers with (a) specific details about realities of poverty, (b) opportunities to discuss and observe the relationship among poverty, teachers, and schools, and (c) examples of children and families from poverty who have positive attributes.